2018
DOI: 10.2106/jbjs.oa.17.00065
|View full text |Cite
|
Sign up to set email alerts
|

Registration and Outcome-Reporting Bias in Randomized Controlled Trials of Distal Radial Fracture Treatment

Abstract: Background:The purpose of the present study was to systematically evaluate the completeness of trial registration and the extent of outcome-reporting bias in modern randomized controlled trials (RCTs) relating to the treatment of distal radial fracture.Methods:With use of 4 databases (PubMed, Cochrane CENTRAL, Embase, and PEDro), this systematic review identified all RCTs of distal radial fracture treatment published from January 1, 2010, to December 31, 2015. We independently determined the registration statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The review identified 78 trials published over a period of 35 years, which is a surprisingly small number. To put this number into context, a systematic review on the treatment of distal radial fractures identified 90 RCTs published over 5 years from 2010 to 2015 (Lee et al., 2018). The trials identified in the present review covered only seven anatomical areas of the hand.…”
Section: Discussionmentioning
confidence: 99%
“…The review identified 78 trials published over a period of 35 years, which is a surprisingly small number. To put this number into context, a systematic review on the treatment of distal radial fractures identified 90 RCTs published over 5 years from 2010 to 2015 (Lee et al., 2018). The trials identified in the present review covered only seven anatomical areas of the hand.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown a similar high prevalence of ORB in RCTs, but no previous study has focused on the contribution of graphical illustrations to ORB [ [6] , [7] , [8] , [18] , [19] , [20] ]. This is very surprising, given the key role that data visualization has assumed in the medical literature since the first principles were historically presented by authors such as Tufte and Cleveland, and particularly with the advent and growth of social media and electronic publishing [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has been further supported by design guidelines such as SPIRIT and PRISMA-P [ 34 , 35 ]. However, these measures have not proven to be the intended panacea, with non-registration of published trials and ORB remaining commonplace [ 6 , 7 , [36] , [37] , [38] , [39] , [40] ]. This inertia has been attributed to a lack of researcher awareness, but stricter enforcement by editorial teams is required, particularly moving away from the publication of un-registered trials or trials registered after outcome collection [ [41] , [42] , [43] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The updated Consolidated Standards of Reporting Trials statement (CONSORT) in 2010 contains clear recommendations for registration and outcome reporting (Schulz et al, 2010). Despite these standards being set, Lee et al (2018) found that only 31% (28/90) of RCTs on DRFs were registered. Only 16 trials specified a primary outcome measure at registration, and seven of these ended up reporting either a different/additional primary outcome or none at all.…”
Section: Discussionmentioning
confidence: 99%